2000
DOI: 10.1021/la9912444
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of C12E4 at the Air−Water Interface:  Adsorption onto a Fresh Interface

Abstract: The adsorption of C12E4 onto a fresh air-water interface was investigated by using video-enhanced pendant bubble tensiometry. From the comparison between the equilibrium surface tension data and the theoretical relaxation profiles predicted by the Frumkin adsorption isotherm, the adsorption process was found to be anticooperative. Dynamic surface tension data for C12E4 molecules absorbing onto a freshly created air-water interface for different bulk concentrations were used for the determination of the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 24 publications
4
93
0
Order By: Relevance
“…Values of D for linear molecules are reported to be some 30% greater than that for substances of spherical molecules (Hsu et al, 2000). It should be pointed out that for salt-free ionic surfactant solutions electrostatic interactions are demonstrated to drastically affect the adsorption kinetics (Diamant & Andelman, 1996).…”
Section: Adsorption Kinetics Parametersmentioning
confidence: 94%
“…Values of D for linear molecules are reported to be some 30% greater than that for substances of spherical molecules (Hsu et al, 2000). It should be pointed out that for salt-free ionic surfactant solutions electrostatic interactions are demonstrated to drastically affect the adsorption kinetics (Diamant & Andelman, 1996).…”
Section: Adsorption Kinetics Parametersmentioning
confidence: 94%
“…activity at low concentrations and an unusual shape of the surface tension isotherms completely incompatible with the Langmuir model. Equilibrium surface and interfacial tension of oxyethylated alcohols (C n EO m ) was studied by different authors and were reported in many papers (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Then Eq. (8) must be iterated to find eq for that range [19]. The red + shows the equilibrium value found using the pattern search algorithm.…”
Section: Results: Transport Parametersmentioning
confidence: 99%
“…The sets include two pendant drops and one pendant bubble study: aqueous sodium oleate (SO) drops in mineral oil, aqueous sodium dodecyl sulfate (SDS) drops in mineral oil, and air bubbles in aqueous C 12 E 4 [19]. We also include two historical studies involving aqueous SDS in air [20,21] where equilibrium surface tension values are determined by foaming [22] and du Noüy ring [23] methods.…”
Section: Results: Transport Parametersmentioning
confidence: 99%
See 1 more Smart Citation